Colloid preloading versus crystalloid preloading to prevent hypotension after spinal anesthesia for cesarean delivery: A protocol for systematic review and meta-analysis. Issue 7 (19th February 2021) - Shang, Yuchao; Li, Huafeng; Ma, Junmei; Tan, Ling; Li, Shuying; Li, Ping; Sheng, Bo; Wang, Rurong
Abstract: Background: Maternal hypotension is the most frequent complication of spinal anesthesia for cesarean delivery, and intravenous fluid preloading is a preventive measure. We aimed to assess the efficacy of colloids versus crystalloids for preloading to reduce the incidence of spinal anesthesia-induced hypotension and vasopressor requirement in healthy parturients during elective cesarean delivery. Methods: We searched the Cochrane Library, MEDLINE and EMBASE to identify all studies published to June, 2019, through OVID and PubMed. We included randomized controlled trials, comparing colloid preloading with crystalloid preloading in women having spinal anesthesia for cesarean delivery. Primary outcomes were the incidence of hypotension and vasopressor requirement. Secondary outcomes included nausea and/or vomiting, neonatal Apgar score, neonatal umbilical blood pH. We used standardized mean differences for expressing continuous outcomes and risk ratios for dichotomous outcomes. Random-effect model was performed to estimate the pooled risk ratios and standardized mean differences. Results: Thirty-three randomized controlled trials contributed data for this meta-analysis. Fewer women experienced hypotension in the colloid group compared with the crystalloid group (risk ratio: 0.72, 95% confidence interval: 0.63–0.82; 2566 women, 32 studies; P  < .00001). The total ephedrine dose required was significantly lower with colloid preloading (standardized mean difference: −0.37, 95% CI: −0.64 to −0.09; 1472 women, 19 studies; P  = .009). Colloid preloading was also associated with fewer phenylephrine requirement compared with crystalloid preloading (standardized mean difference: -0.54, 95% CI: -0.82 to -0.25; 169 women; P  = .0002). The incidence of nausea and/or vomiting was significantly reduced with colloid preloading (risk ratio: 0.72, 95% CI: 0.55–0.95; 1601 women, 20 studies; P  = .02). However, the incidence of 1-minute Apgar score < 7, umbilical artery pH < 7.2 and umbilical vein pH < 7.2 were not statistically different between groups. Conclusions: Colloid preloading is superior to crystalloid preloading in reducing the incidence of hypotension induced by spinal anesthesia and vasopressor requirement in the healthy parturients undergoing elective cesarean delivery. The PROSPERO registration number: CRD42018096402. Abstract : Supplemental Digital Content is available in the text